2010
DOI: 10.1007/s10637-010-9518-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nur77 induced by an n-butylidenephthalide derivative promotes apoptosis and inhibits cell growth in oral squamous cell carcinoma

Abstract: In spite of numerous advances, the 5-year survival rate for head and neck squamous cell cancer has remained largely stagnant and few new anti-tumor drugs have been developed. PCH4, a derivative of n-butylidenephthalide, has been investigated for its anti-tumor effects on oral squamous cell carcinoma (OSCC). The aim of this study was to investigate the anti-tumor mechanism of a potential target gene, Nur77, in OSCC cells, which can be induced by PCH4 treatment. Data show that PCH4 promoted Nur77 translocation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
(27 reference statements)
1
24
0
Order By: Relevance
“…In OSCC, NR4A1 activated through the MAPK signaling pathway can induce apoptosis (23). The present study demonstrated that the combination of the upregulation of NR4A1 and MAP2K5 increased the level of apoptosis subsequent to WWOX overexpression in Tca8113 cells.…”
Section: Discussionsupporting
confidence: 50%
“…In OSCC, NR4A1 activated through the MAPK signaling pathway can induce apoptosis (23). The present study demonstrated that the combination of the upregulation of NR4A1 and MAP2K5 increased the level of apoptosis subsequent to WWOX overexpression in Tca8113 cells.…”
Section: Discussionsupporting
confidence: 50%
“…Their ability to produce structurally diverse and biologically significant monomeric and dimeric phthalide metabolites is well documented [1,2]. Previous pharmacological activity studies revealed that these compounds display anti-proliferative [3,4], anti-inflammatory [5][6][7], anti-thrombus [8], neuroprotective [9][10][11], anti-tumor [12,13], and anti-spasmodic effects. In recent years, the bioactivities of these compounds have attracted a great interest and extensive research has been carried out to characterize the molecular mechanism(s) behind their activity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in response to n-Butylidenephthalide induced cell death signals, NR4A1 translocates into mitochondria to enhance apoptosis Liu et al, 2012).…”
Section: Localisationmentioning
confidence: 99%
“…For example, glioblastoma multiforme is inhibited by local interstitial delivery of z-butylidenephthalide, which enhances NR4A1 expression and translocation into mitochondria Lin et al, 2008). Nbutylidenephthalide derivative also inhibit cell growth in hepatocellular carcinoma, oral squamous cell carcinoma and balloon injured rat carotid artery by inducing apoptosis Liu et al, 2011;Liu et al, 2012). Moreover, 1,1-Bis(3'-indolyl)-1-(psubstituted phenyl)methanes induce apoptosis through NR4A1 activation in cultured pancreatic carcinoma cells (Chintharlapalli et al, 2005).…”
Section: Cancer and Clinical Translationmentioning
confidence: 99%